Brain mGluR5 in Shank3B−/− Mice Studied With in vivo [18F]FPEB PET Imaging and ex vivo Immunoblotting - Cai, Guohong; Wang, Mengmeng; Wang, Shuailiang; Liu, Yi; Zhao, Yan; Zhu, Yuanyuan; Zhao, Suo; Zhang, Ming; Guo, Baolin; Yao, Han; Wang, Wenting; Wang, Jing; et al. (Frontiers in Psychiatry, 2019)
Although several studies have found that metabotropic glutamate 5 receptor (mGluR5) may play an important role in autism spectrum disorders (ASD), the mechanisms remain unclear. Here, we used a Shank3 gene complete knockout mouse model (Shank3B−/−) to explore the change in mGluR5 in the brain. To assess whether deletion of Shank3 in mice results in ASD-like behavior, we conducted a battery of behavioral experiments to characterize Shank3B−/− mice, including repetitive grooming behavior tests, three-chamber tests and resident-intruder tests. Wild-type C57/BL6 and Shank3B−/− mice underwent PET scans with [18F]FPEB, which was highly specific to mGluR5. Mouse brains were extracted post-scan, and mGluR5 protein levels were assessed by immunoblotting. The binding potential (BPnd) of mGluR5 was rich in the hippocampus, thalamus, striatum, and amygdala. More importantly, Shank3B−/− mice showed significantly increased BPnd compared to the control mice in these brain regions. Immunoblotting revealed elevated mGluR5 levels in the hippocampus, thalamus, and amygdala but not in the striatum compared with control mice. These findings indicated that [18F]FPEB could visualize mGluR5 in the mouse brain. The deficiency of Shank3 can impair mGluR5 expression in multiple brain regions. Future work is also needed to understand the reasons for different results between in vivo PET and ex vivo immunoblotting.